Weed management in ash gourd (Benincasa hispida (Thunb.) Cogn.) - Sajeera C Chathoth (Department of Agronomy, College of Horticulture, 2014)
A field experiment on “Weed management in ash gourd” [Benincasa hispida (Thunb.) Cogn.] was conducted during July to November 2013 at Krishi Vigyan Kendra farm at KAU campus, Thrissur using the variety KAU local. The main objectives of the study were to compare the efficacy of cultural, physical and chemical methods of weed control and their combinations to arrive at an integrated weed management practice in ash gourd and to work out the economics of various weed management practices. The experiment was laid out in a Randomised Block Design with three replications. The treatments included pre- emergence application of oxyfluorfen @ 0.2 kg/ha, pre emergence application of pendimethalin @ 1.5 kg/ha, pre emergence application of oxyfluorfen @ 0.2 kg/ha followed by post emergence directed application of glyphosate @ 0.8 kg/ha, pre emergence application of pendimethalin @1.5 kg/ha followed by post emergence directed application of glyphosate @ 0.8 kg/ha, mulching with coconut fronds, mulching with polythene sheet, weeding using tiller, manual weeding by hoeing and no weeding. Major weeds found in experimental field were dicots which comprised of Alternanthera betzikiana, Borreria hispida, Celosia argentia etc. Pennisetum pedicellatum was the dominant grass species followed by Brachiaria sp. Plastic mulching of the field resulted in almost cent percent weed control efficiency. The lowest weed dry weight and highest nutrient uptake was recorded in plastic mulched plot which was statistically superior to all other treatments at all stages of observation. N, P and K uptake by weeds was higher in unweeded control and lower in plastic mulched, and the uptake increased from 30 DAS to harvest stage. The plant growth parameters like branches/vine and leaves/vine were significantly high in plastic mulched plots followed by hand weeded plot. The highest fruit yield (22,680 kg/ha) and seed yield (212 kg/ha) was recorded in plastic mulched plots which was statistically superior to all other treatments. Manual weeding was the next best practice and resulted in 16.54 t/ha fruit yield and 144.12 kg/ha of seed yield. Weed competition resulted in 91.5 per cent reduction in crop yield. Though total cost of cultivation was the highest for plastic mulching, it resulted in the highest net return and B:C ratio (2.73). Coconut frond mulching cannot be recommended as a weed control measure as it was found ineffective in suppressing weed growth and no net profit could be obtained. Application of pre-emergence herbicide alone could not take care of weed problem and hence can be recommended only for weed control during a short span of 30 days. The two pre-emergence herbicides tried viz; oxyfluorfen and pendimethalin had similar performance. Even a follow up spray of post emergence herbicide was found not sufficient to enhance the yield level. However this can be integrated with other weed control methods like manual weeding or mechanical weeding. It is concluded that plastic mulching is the best method for weed control in ash gourd in areas where weed problem is very severe